2019
DOI: 10.5210/fm.v24i9.10105
|View full text |Cite
|
Sign up to set email alerts
|

Autism and online recruiting methods: A comparison of Mechanical Turk and discussion forums

Abstract: In a study by a team at the intersection of information and communication sciences and disorders, researchers worked to design an interactive, online professional development system for academic librarians to better serve students with autism spectrum disorder (ASD). In creating this program, it was imperative to have stakeholder input and support; recruiting members of this population, students with ASD, was critical. Amazon’s Mechanical Turk and online discussion forums, including Reddit, were used for recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Qualtrics, an online survey platform, was used to provide surveys and collect participant data. These online data collection methods were used because these and other online sampling methods appear to be preferred by participants with ASD because they can participate anonymously, from wherever they choose, without needing to disclose their ASD diagnosis in front of others (Anderson et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Qualtrics, an online survey platform, was used to provide surveys and collect participant data. These online data collection methods were used because these and other online sampling methods appear to be preferred by participants with ASD because they can participate anonymously, from wherever they choose, without needing to disclose their ASD diagnosis in front of others (Anderson et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The third phase of recruitment occurred via a posting on Amazon's Mechanical Turk (MTurk). MTurk has been used in research since 2005 (Buhrmester et al, 2011) and is described as an effective method to recruit hard-to-reach populations, including those with disabilities (Anderson et al, 2019;Smith et al, 2015). Research has also shown that MTurk participants are more attentive, thus perform better than comparison groups on completing online surveys (Hauser & Schwarz, 2016), which has positive implications on the benefits of using MTurk samples in social science research (Chandler et al, 2014).…”
Section: Recruitmentmentioning
confidence: 99%